Effects of the Adult Attachment Projective Picture System on Oxytocin and Cortisol Blood Levels in Mothers - Krause, Sabrina; Pokorny, Dan; Schury, Katharina; Doyen-Waldecker, Cornelia; Hulbert, Anna-Lena; Karabatsiakis, Alexander; Kolassa, Iris-Tatjana; Gündel, Harald; Waller, Christiane; Buchheim, Anna (Frontiers in Human Neuroscience, 2016)
Oxytocin, a small neuropeptide of nine amino acids, has been characterized as the “hormone of affiliation” and is stimulated, for instance, in mothers when interacting with their offspring. Variations in maternal oxytocin levels were reported to predict differences in the quality of care provided by mothers. In this study, the Adult Attachment Projective Picture System (AAP) as a valid measure to assess attachment representations was used as an activating attachment-related stimulus. We investigated whether the AAP induces a release of oxytocin in mothers with a secure attachment representation and a stress-related cortisol response in mothers with an insecure attachment representation. Therefore, pre-post effects of AAP administration on plasma oxytocin and serum cortisol levels were investigated in n = 44 mothers 3 months after parturition. Oxytocin levels increased from pre to post by the significant majority of 73% participants (p = .004) and cortisol decreased by the significant majority of 73% participants (p = .004). Interestingly, no association between alterations in oxytocin and cortisol were found; this suggests taking a model of two independent processes into considerations. These results show that the AAP test procedure induces an oxytocin response. Concerning the results within the four AAP representation subgroups, our hypothesis of a particularly strong increase in oxytocin in secure mothers was not confirmed; however, in secure mothers we observed a particularly strong decrease in cortisol, consistent with our hypotheses. Effect sizes are reported, allowing the replication of results in a larger study with sufficient sample size to draw final conclusions with respect to differences in OT and cortisol alterations depending on attachment representation. When interpreting the results, one should keep in mind that this study investigated lactating mothers. Thus, the generalizability of results is limited and future studies should investigate non-lactating healthy females as well as males and include a control stimulus condition.